Evaluation and Comparison of Salivary Annexin-1 Levels in Type-2 Diabetic Patients with and without Generalized Periodontitis - Amit Bajirao Jadhav (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study evaluates and compares salivary Annexin-1 levels in Type-2 diabetic patients with and without generalized periodontitis. Saliva samples from 100 participants were analyzed using ELISA. The results indicated significantly lower Annexin-1 levels in diabetic patients with periodontitis compared to those without. These findings suggest that decreased Annexin-1 levels are associated with periodontal inflammation in Type-2 diabetic patients, highlighting its potential as a biomarker for periodontal disease in this population. The objective of this study is to evaluate and compare salivary Annexin-1 levels in Type-2 diabetic patients with and without generalized periodontitis to elucidate the relationship between this inflammatory biomarker and periodontal disease in the context of diabetes. In the methods section, a cross-sectional study was conducted involving two groups of Type-2 diabetic patients: those with generalized periodontitis (Group A) and those without periodontitis (Group B). Unstimulated saliva samples were collected from all participants, and Annexin-1 levels were quantified using enzyme-linked immunosorbent assay (ELISA). Statistical analyses were performed to compare Annexin-1 levels between the groups and to explore correlations with clinical periodontal parameters and glycaemic control. The results included 50 participants in each group. Salivary Annexin-1 levels were significantly lower in Group A compared to Group B (p<0.05). Annexin-1 levels were negatively correlated with probing depth and clinical attachment loss but showed no significant correlation with HbA1c levels. In conclusion, the findings suggest that decreased salivary Annexin-1 levels are associated with generalized periodontitis in Type-2 diabetic patients. Annexin-1 may serve as a potential biomarker for inflammation and periodontal disease in this population.